Analyzing Oct4 conserved domains in lower vertebrates - Sousa, Cátia Alexandra Ferreira de (2008)
Oct-4 is a POU-V domain transcription factor which regulates pluripotency in mammals and expressed in ES cells and germ cells, and was believed to be a gene unique to mammals. Recently, it has been demonstrated to be present in the genomes of Xenopus, zebrafish, sturgeon and axolotl. It has been shown that Oct-4 has three transactivation domains, (N), POU and (C), with DNA binding mediated through the POU domain. It was unknown how the activity of these domains has been retained through evolution and how they collectively function to control pluripotency. This study is new and is the first to analyse the functional conservation of these Oct-4 homologues, and their regulation molecular. Three different assays were developed to study Oct4 functionality: 1) A transactivation assay in which the function of Oct4 protein over-expression on a known Oct4-target sequence was assessed (by luciferase assay using the p6Wtk-luc reporter containing Oct4 binding sites); 2) A heterologous transactivation assay in which the function of specific Oct4 domains by linking them to Gal4-DNA binding domain was specifically assessed (DBD) (by luciferase assay using the pGal4-lux reporter). 3) The subcellular localization of Oct-4 homologues (generating two constructs; either full’ length or POU domain, fused to Green fluorescent protein (GFP). This study showed the coexistence of DBD conflicts with Oct4 resulting in a decrease on its transactivation capacity when compared to their native state. Oct-4 function generally conserved among species, with Xenopus Oct91 being the Oct-4 homologue with a transactivation function more similar to mouse Oct-4. Between (C) and (N) transactivation domains linked to DBD, the (C) domain was the one with more activity. The (C) domain is cell-type specific regulated by phosphorylation events, while the (N) domain suffers sumoylation. These two regulatory mechanisms are shared in all Oct-4 homologues. It was also possible to conclude that Oct-4 protein is nuclei transcribed. This project opens many possible studies in Oct-4 regulation.